Ernest Ansermet et Les fondements de la musique - Piguet, J.-Claude 1924-2000 (Lausanne Payot, 1964)
Ernest Ansermet, conductor of the Ballets Russes from 1915 to 1923 and founder of the Orchestre de la Suisse Romande, shared with Wilhelm Furtwängler the concern for a fundamental reflection on the relationship between man and music. Circumstances forced him to take sides from the very beginning, in Montreux in 1912, when he fought to impose Bartók, Honegger and especially his friend Stravinsky in his concerts. On the other hand, he surprised avant-garde circles by taking a hostile position to atonal music at the end of his life. In the meantime, in addition to conducting and touring in the United States, Latin America and Japan, Ansermet was engaged in writing a very extensive work. From 1943 to 1961, eighteen years of reflection and work gave rise, alongside his international career, to a treatise that has scarcely had any equivalent in this century, 'Les Fondements de la musique dans la conscience humaine', a veritable spiritual testament, an approach to tonality that is at once physiological, mathematical, philosophical and metaphysical, a spiritual guide for the interpreter faced with an ethical choice and a global vision of man.
Keywords: Ansermet, Ernest -- 1883-1969; Music philosophy and esthetics; Switzerland